Interaction Behavior on Edmodo in Biology: Integrating UTAUT Model - Shakila Mohamad Ashari, Zaidatul; Azmi, Nurhazirah; Yaacob, Yanti; Hajar Noor Alshurdin, Siti; fatt Low, Kim (International Journal of Engineering and Technology, 2018)
Integration of Edmodo, a social network educational platform allows educators-students to communicate, being in real-time discussion and collaborate in a significant approach. Edmodo yet, is still not dominant in Malaysia educational practices. The purpose of this research is to determine the students’ interaction behavior in learning by addition of Edmodo as subsidiary tool in Biology using Unified Theory of Acceptance and Use of Technology (UTAUT) as theoretical framework. Sample of study consists of 74 undergraduate students who were registered in Biology code. Self-access learning module was given to the samples for 2 consecutive weeks during early semester followed by the questionnaire at the end of semester. Data has been collected using a 5 point Likert scale with the element of main construct in UTAUT. Pearson correlation and linear regression were performed to analyze the data. It was found that performance expectancy and effort expectancy exhibited positive significant effect on interaction behavior towards Edmodo, while social influence and facilitating conditions had no significant effect.    .